(untitled) (CIPEEX, 2024)
Criminal organizations in Brazil have a long history, from the time of Lampião to contemporary criminal factions such as the Comando Vermelho and the Primeiro Comando da Capital. These organizations have infiltrated various sectors of power in organized civil society. At the same time, Brazilian legislation has evolved to combat these entities, starting with the Palermo Convention and culminating in Law No. 12,850/2013, with adjustments from the Anti-Crime Package Law (Law No. 13,964/2019). This study aims to analyze the applicability of Law No. 12.850/2013 in the fight against criminal organizations, addressing the historical evolution of criminal factions in Brazil, the evolution of the relevant legislation and the ways to combat these organizations. The deductive and dialectical method was adopted, with qualitative, descriptive and explanatory research. The research included a bibliographical review of academic literature, analysis of legal documents and case studies to better understand the effectiveness of laws and practices in combating criminal organizations. The results showed that Brazilian legislation has continuously adapted to changes in the activities of criminal organizations. Law No. 12.850/2013, in particular, has provided a more robust legal framework for combating the activities of these factions. The modifications introduced by the Anti-Crime Package Law have further improved the effectiveness of the legislation. However, despite these legal advances, the practical application of the law faces significant challenges, such as corruption and the lack of adequate resources for policy implementation. The analysis showed that although legislation has advanced considerably, its practical applicability still needs improvement. The effectiveness of laws depends not only on their content, but also on the rigorous implementation and ongoing support of the institutions involved in the fight against organized crime. The research highlighted the importance of a multi-faceted approach, which includes improving the infrastructure of security forces, fighting corruption and strengthening judicial and police institutions. In order to effectively confront criminal organizations, closer collaboration between different levels of government and sectors of society is essential. The study concludes that although Law No. 12.850/2013 has provided important legal tools to combat criminal organizations, the full realization of its benefits requires consistent and sustained practical application. The continued evolution of legislation and combat strategies is crucial to tackling the growing sophistication of criminal organizations in Brazil.